The Corporate Income Tax in Colombia: its Effective Rate and its Relationship with Investment (2020)
In Colombia it is traditional that discussions about tax reforms indicate that corporate taxation is so burdensome that it drives away the investment and slows down economic growth, which is why preferential tax treatments or tax cuts are promoted. This is, in fact, what is behind the most recent tax reform in Colombia, which was named as the Financing Law in 2018, but this research shows two facts. The first one is that the effective rate of Corporate Income Tax is not as high as it is stressed in Colombia by the media, economic unions and many politicians, for which we take into account tax reporting data provided by the Colombian tax administration office (DIAN) for 2016. The second issue is related to the generally accepted hypothesis that taxation discourages investment, which is denied through a data panel analysis across 109 countries (including Colombia) and the period 2006-2015.